Berdirinya dinasti Bani Abbas - Safitri, Yupita; Afrizal M; Sawaluddin (Karoteh Utama, 2024)
This study aims to provide a comprehensive overview of the history behind the establishment of the Abbasid Dynasty. It employs a historical approach using the historical method, which includes the collection, verification, interpretation, and presentation of data from reliable sources. The findings indicate that the establishment of the Abbasid Dynasty was influenced by several key factors. First, widespread dissatisfaction with the governance of the Umayyad Dynasty, which was perceived as unjust and authoritarian. Second, the ambition of the Abbasid family, who believed they had stronger legitimacy to lead the caliphate due to their closer lineage to the Prophet Muhammad (peace be upon him) compared to the Umayyads. Third, the forced seizure of power by the Umayyads during the tragic Battle of Siffin. Fourth, the lavish lifestyle of some Umayyad caliphs, which often deviated from Islamic values in terms of worship and conduct. This study is expected to contribute significantly to understanding the political and social dynamics of the early Abbasid era.